Antioxidant and anticancer properties of fucoidan isolated from Saccharina Japonica brown algae - Qiulin Yue; Yongxuan Liu; Fujia Li; Tao Hong; Shousen Guo; Mengrui Cai; Lin Zhao; Le Su; Song Zhang; Chen Zhao; Kunlun Li (Scientific Reports)
Abstract Fucoidan is a fucose-rich sulfated polysaccharide that has gained attention owing to its various biological activities. In this study, fucoidan was isolated from Saccharina japonica using an enzyme-assisted method, and its antioxidant and anti-hepatocarcinoma effects were evaluated. The fucoidan was a 112.8 kDa polysaccharide comprising seven monosaccharides: fucose, xylose, glucuronic acid, rhamnose, glucose, mannose, and galactose. The main chain residues were (1 → 3)-α-L-Fucp and (1 → 4)-α-L-Fucp units with sulfate groups at the C-2/C-4 positions of the (1 → 3)-α-L-Fucp residues. S. japonica fucoidans showed excellent antioxidant potency with values of 1.02 mg TE/g and 5.39 mg TE/g for the ABTS and FRAP assays, respectively. Additionally, they exerted antitumor efficacy and low systemic toxicity in H22 tumor-bearing mice, with a tumor inhibition rate of 42.93%. Furthermore, it significantly inhibited tumor angiogenesis and reduced pro-inflammatory cytokines levels (IL-1β, IL-6, and TNF-α). Our results suggest that fucoidan isolated from S. japonica possesses potent antioxidant and anticancer properties and may be used as a potential agent for hepatocellular carcinoma treatment.